Influence of Initial Conditions on Unsaturated Groundwater Flow Models - Mohd Taib, Aizat; Raihan Taha, Mohd; Zulaika Abang Hasbollah, Dayang (International Journal of Engineering and Technology, 2019)
Slope failure in unsaturated soils is common in tropical countries due to the seasonal pattern of abundant rainfall preceding a period of prolonged drying. Much research has been undertaken to understand the behaviour of unsaturated slopes and reduce the number of catastrophic failures. The initial conditions are important factors in numerical modelling of the groundwater flow yet rarely considered in detail in the literature. This paper presents a parametric study of the initial conditions at a slope in Bukit Timah, Singapore. The intensity and duration of rainfall are varied to assess the effect on the pore-water pressure in the slope. The generated pore-water pressure profile is compared with field measurements and previous numerical studies. It is discovered that a low rainfall, with an intensity of 1x10-7 m/s over a period of 62 days, results in initial pore-water pressure which is consistent with data recorded at the field. Unlike the duration, changes in the rainfall intensity are shown to have a significant effect on the pore-water pressure in the slope. This study, therefore, demonstrates the importance of determining appropriate initial conditions in unsaturated groundwater flow analysis. Â Â Â